Da Atenas à Jamaica brasileira: imaginários sobre São Luís na mídia maranhense - Santos, Samuel Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
Approaching about a study in the cut of the speech analysis from French line that sees the text (verbal and non-verbal) interlacing of voices that stabilize according to the ideology for communicating, this present study makes a press cutting from printed media that constitute the epithets of Brazilian Athenas and Brazilian Jamaica the city of São Luis of Maranhão. This interlacing is catched in the materiality of the texts from the newspapers The Imparcial and The State of Maranhão, that propoce the effects of sence for modelling according to the culture of the folk's identitity, promoting the imposbility of the individual gets out from the game or the sign order or from the ideology. Through from remission to the collective symbole, the media promove an absolute unit from the enuciations that circle in the vehicles and introduce to the collectivity the identitity speeches that will feed the social imaginary of the folk from Maranhão the way of Athenas to the Brazilian Jamaica

Supondo-se um trabalho no talhe da Análise do Discurso, de linha francesa, que vê o texto (verbal e não-verbal) como entrelaçamento de vozes que se estabilizam ideologicamente para comunicar, o presente estudo faz um recorte da mídia impressa que constitui os epítetos de Atenas Brasileira e Jamaica Brasileira à cidade de São Luís do Maranhão. Esse entrelaçamento é apanhado na materialidade dos textos dos jornais O Imparcial e o Estado do Maranhão que propõem os efeitos de sentidos para modelar culturalmente a identidade de um povo, promovendo a impossibilidade do sujeito de escapar ao jogo da ordem do signo e da ideologia. Através da remissão a símbolos coletivos, a mídia promove uma unidade absoluta aos enunciados que circulam nos veículos e introjetam para a coletividade os discursos identitários que irão alimentar o imaginário social do povo maranhense num percurso de Atenas a Jamaica Brasileira
Keywords: Linguística; Midia (Publicidade); Identidade; Ideologia e arte; Imaginario; Linguistic